Hatchability of zooplankton egg in water after irradiation with pulsed intense relativistic electron beam. (8th December 2017) - Shoji, Kenta; Takahashi, Kazumasa; Sasaki, Toru; Kikuchi, Takashi; Harada, Nob.; Imada, Go
Abstract : Hatchability of zooplankton ( Artemia Salina ) eggs in water irradiated with pulsed intense relativistic electron beam (PIREB) was studied. The PIREB with a kinetic energy of up to 6 MeV, a peak current of −500 A and pulse duration of 80 ns (FWHM) is generated by using the intense pulsed power generator "ETIGO‐III." The hatchability after PIREB irradiations reduced up to almost 0% in the higher‐dose region. Also, the hatchability on the outside of the penetration depth of PIREB reduced in comparison to one without PIREB irradiation.